2021
DOI: 10.1002/ehf2.13622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the sodium‐glucose cotransporter 2 inhibitor empagliflozin on vascular function in patients with chronic heart failure

Abstract: Aims Impairment of vascular function contributes to the progression of chronic heart failure (HF) by increasing the afterload. Treatment with selective sodium-glucose cotransporter 2 (SGLT2) inhibitors improves the prognosis of HF, but the precise mechanisms remain unclear. The aim of this study was to analyse the effect of empagliflozin on vascular function in patients with HF. Methods and resultsIn an investigator initiated, double-blind, randomized, placebo-controlled, parallel-group, clinical study, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…When we also excluded the other trial performed in the HFrEF population, 28 we observed that SGLT-2 inhibitor compared to control led to a significant decrease in PWV by 0.17 m/s (MD = −0.17, 95% CI −0.31 to −0.04, I 2 = 0%, p = 0.01), with complete elimination of the observed heterogeneity. Of note, this analysis corresponds to the effect of SGLT-2 inhibitors on PWV in subjects with T2DM at background, showing a favorable effect on that cardiovascular risk marker.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…When we also excluded the other trial performed in the HFrEF population, 28 we observed that SGLT-2 inhibitor compared to control led to a significant decrease in PWV by 0.17 m/s (MD = −0.17, 95% CI −0.31 to −0.04, I 2 = 0%, p = 0.01), with complete elimination of the observed heterogeneity. Of note, this analysis corresponds to the effect of SGLT-2 inhibitors on PWV in subjects with T2DM at background, showing a favorable effect on that cardiovascular risk marker.…”
Section: Resultsmentioning
confidence: 92%
“…We pooled data from six trials in a total of 452 enrolled participants assigned either to SGLT-2 inhibitor or control. [26][27][28][29][30][31] All trials enrolled subjects with T2DM except for two trials performed by Requena-Ibáñez et al, 27 in which none of the participants had a prior diagnosis of T2DM, and by Kolwelter et al, 28 who enrolled subjects with a prior diagnosis of heart failure with reduced ejection fraction (HFrEF), from whom less than one-fourth suffered from T2DM prior to inclusion in the trial. A thorough description of participants' baseline characteristics of interest along with PWV analysis methods is provided in Table 1.…”
Section: Results Of Search and Trial Characteristicsmentioning
confidence: 99%
“…We showed reduced office BP and improved metabolic control, findings well described in our previous studies [ 22 , 35 ]. In a previously published analysis that focused on vascular effects in patients with CHF, we showed a significant decrease in central systolic BP and central pulse pressure under resting conditions as well as under 24-h ambulatory conditions after 1 and 3 months of treatment with empagliflozin [ 17 ]. These effects are mediated by the reduction of the preload through natriuresis and osmotic diuresis as well as of the afterload through reducing the arterial stiffness (indicated by the decrease in central BP and improving vascular function [ 17 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). The results on vascular parameters under 24-h daily conditions as well as under laboratory conditions were already previously published [ 17 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Vascular metrics such as central systolic blood pressure (cSBP), central pulse pressure (cPP), forward pressure height (FPH), and reflected pressure pulse height (RPH) under basal conditions decreased in the EMPA therapy group (n = 45) after one and three months. The decreased afterload of the left ventricle caused by greater arterial and aortic compliance perhaps led to a better prognosis seen in HF patients taking SGLT2 inhibition [ 21 ].…”
Section: Reviewmentioning
confidence: 99%